Dielectric percolation in ceramic matrix composites - A. N. Rybyanets; N. A. Shvetsova; I. A. Shvetsov; N. A. Kolpacheva (Journal of Advanced Dielectrics)
This paper presents the results of an experimental study of the percolation behavior of the complex dielectric constant of ceramic matrix composites (CMC). Samples of piezoactive CMC were obtained by joint sintering of synthesized PZT piezoceramic powder (matrix) and crushed particles of sintered PZT piezoceramics (filler) of different compositions. The experimental dependencies of real and imaginary parts of the complex dielectric constant of CMC on the porosity of piezoceramic matrix and volume content of ceramic filler particles were measured and analyzed. It was shown that the additional porosity of the ceramic matrix resulting from sintering of the CMC masks the dielectric percolation transition, that actually occurs at the volume concentration of ceramic filler close to percolation threshold (V ∼ 1/3).